Finding Balance: The Impact of Emotional Variability on the Stress and Well-Being of Collegiate Dance Students - Richels, Kelsey (My University, 2021)
The purpose of this qualitative longitudinal study involving 18 undergraduate dance majors was to address the gaps in the empirical literature regarding the potential impact of emotional variability on the stress and well-being of collegiate dance students. Specifically, using daily, repeated measures over the course of 4 weeks in the Fall semester of 2020, combined with additional surveys early and later in the semester, I examined how differences in affect spin and affect pulse were related to differences in well-being, including but not limited to measures of stress (both distress [i.e., strain] and eustress [i.e., thriving, challenge]), subjective well-being, and role conflict. In particular, the use of robust qualitative data gathered from open-ended questions regarding emotional experiences and perceptions of the impact (i.e., harm versus benefit) of emotions were examined in tandem with the quantitative data in order to produce a full understanding of the experience of emotional fluctuations in dance. Additionally, I examined if differences exist between ballet (n = 10) and modern dancers (n = 8). In general, dancers reported experiencing a plethora of stressors, primarily associated with the experience of negative emotions. These negative emotions impacted their ability to succeed as collegiate dance students by impacting their ability to maintain a sense of balance and by amplifying feelings of existing strain. On the positive side, emotions were perceived by dancers in the current study to contribute to their emotional artistry, which participants considered to be a key aspect of their performance. Results showed greater strain and negative emotional events by those higher in affect variability, particularly affect spin. This extended into emphasis effects, with those majoring in modern dance exhibiting higher levels of affect spin as well as more negative outcomes in terms of strain and less well-being compared to ballet majors. Results are discussed in terms of future considerations for continued research and practical intervention.
Keywords: affect variability; stress; well being; dance